Women in Sustainable Education: Glass Ceiling among Female Schools Principals in Indonesia - Juwitasari, Reni (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
Sex segregation remains happening in the education realm. In the 21st century, Indonesian women's participation in the public sphere still becomes an issue, especially leadership. Women are perceived as the second class of society, even obtaining the negative stereotype of incapable leaders, which the myth of leadership belongs to men's world. As an oxymoron, women are